Should there be a World Health Assembly resolution for malaria eradication? Opinion against - John, T. Jacob (Malar J, 2019)
A resolution for eradicating malaria, if passed by the World Health Assembly (WHA), will have a distracting effect on all countries with malaria. The continued prevalence of malaria is indicative of weak public health infrastructure. True, smallpox was eradicated by international efforts following WHA resolution: the success factor was primary prevention using a safe and effective vaccine. A resolution to eradicate polio was passed in 1988, with a target year of 2000, but even in 2019 success is not within reach. Public health experts are hesitant to move forward with measles eradication before polio is eradicated. Country by country elimination of malaria is a better way, ensuring the strengthening of public health infrastructure, with many other health benefits.